The feasibility of the mid-rise Christian Memorial building complex as a new development in Davao City - Soberano, Hazel L. (2015)
As death rates and population size continue to increase, service facilities that would accommodate its requirements should also be added in response. Congestion and shortage of lots for the deceased are problems that Davao City is experiencing nowadays. Thus, the idea of a new type of development which aims to address the abovementioned issues, flourishes. Services to offer, additional wanted spaces as demanded by the respondents, and financial conditions are the major concerns of this study hence, the investigation on the feasibility of a mid-rise Christian memorial building complex in Davao City. Results from the primary and secondary data collected, show that the proposal is marketable. A demand for additional funeral homes and columbarium has been established. Mid-rise facilities with the same function were also proven acceptable to the respondents. The affordability of funerary services is a major consideration to the design of the new development. The study has found that with a market scheme projection within 5-year payback period, the return on investment is at 19% with a positive annual cash flow of P232,400,878.00 at full occupancy. The study recommends intensive business studies and models to be further explored.